2018
DOI: 10.1007/s10068-018-0379-0
|View full text |Cite
|
Sign up to set email alerts
|

Sialoglycoprotein from Gadous morhua eggs improve high bone turnover activity via down-regulating BMP-2/Smads and Wnt/β-catenin signal pathways

Abstract: The effect of sialoglycoprotein isolated from Gadous morhua eggs (Gm-SGP) on ovariectomized (OVX) induced osteoporosis, which is characterized by high bone turnover activity was investigated. Results revealed that Gm-SGP significantly increased bone mineral density, enhanced bone biomechanical properties and repaired the microstructure of the trabecular bone. Also, the treatment with Gm-SGP remarkably decreased biochemical marker contents or activities, such as serum BALP, PICP, BMP-2, TrACP, Cath-K, urine Ca … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…At the molecular level, the process of bone formation and bone remodeling involves a variety of signaling pathways, and they interact with each other to play a fine regulatory role in complex regulatory network systems. Studies have shown that Wnt/b-catenin signaling pathway [36], BMP-2 signaling pathway [37], and OPG/RANKL signaling pathway [38] play important regulatory roles in bone formation and bone remodeling [39]. The BMP-2 signaling pathway process has 2 roles in the cell.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the molecular level, the process of bone formation and bone remodeling involves a variety of signaling pathways, and they interact with each other to play a fine regulatory role in complex regulatory network systems. Studies have shown that Wnt/b-catenin signaling pathway [36], BMP-2 signaling pathway [37], and OPG/RANKL signaling pathway [38] play important regulatory roles in bone formation and bone remodeling [39]. The BMP-2 signaling pathway process has 2 roles in the cell.…”
Section: Discussionmentioning
confidence: 99%
“…The BMP-2 signaling pathway process has 2 roles in the cell. One is to transfer the external growthpromoting signals to the nucleus via Smads to promote osteogenic differentiation [37]. The other is the MAPK signaling pathway, which also includes 3 signaling pathways: the extracellular signal-regulated kinase (ERK) signaling pathway, the c-Jun N-terminal kinase (JNK) signaling pathway, and the p38 signaling pathway [40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…The NF‐κB signaling pathway classically induces osteoclastogenesis by upregulating the expression of genes involved with resorption of bone contents such as TRAP, Cath‐K, NFATc1 TRAF6, and MMP‐9 (Rachner et al, 2011). In some studies, SGPs inhibited osteoclastogenesis and OP in OVX rats via modulation of Wnt/β‐catenin (Wang et al, 2016) and BMP‐2/Smads (Wang, Han, Wang, Wang, & Wang, 2018) signaling pathways, in addition to the blocking of NF‐κB signaling in OVX rats after 30‐day treatment (Xia et al, 2016). Furthermore, the bone health‐promoting properties of SGPs also extended to the enhancement of bone formation and repair of fractured bones via induction of angiogenesis (Wang, Han, Wang, Li, et al, 2018; Zhan et al, 2017).…”
Section: Osteo‐modulatory Properties Of Food Proteins and Peptidesmentioning
confidence: 99%
“…Sialoglycoprotein, a glycoprotein characterized by high sialic acid (SA) amounts, is widely present in many organisms, especially swiftlet's nest and fish egg (Wang et al., 2008). Sialic acid is the main active component of sialoglycoproteins, which has been proved a variety of biologic activities in improving cardiovascular diseases, inflammation, fracture healing, and cognitive capability (Wang et al., 2018; Xia et al., 2015; Zhan et al., 2017). Dietary intake of SA‐rich bird's nest could improve the oxidative stress in neuroblastoma cells induced by H 2 O 2 (Hou et al., 2015).…”
Section: Introductionmentioning
confidence: 99%